Biofuels : biotechnology, chemistry, and sustainable development - Mousdale, David M. (CRC Press, 2008)
Exploring the scientific underpinnings for the commercialisation of lignocellulosic ethanol, this book begins with the historical context, examining the political and economic pressures that fostered the first large-scale production and use of bioethanol.